Parental divorce and smoking dependence in Lebanese adolescents: the mediating effect of mental health problems - Vanessa Azzi; Katia Iskandar; Sahar Obeid; Souheil Hallit (BMC, 2022)
Abstract Background Lebanon has the highest prevalence estimates among Middle Eastern countries and Arab women regarding cigarette smoking, with 43% of men and 28% of women involved in such trends. Marital disruption is a tremendous source of irritability and discomfort that may hinder a child's healthy development, creating perturbing distress and increasing disobedience that may exacerbate smoking addiction. Additionally, Lebanese adolescents are inflicted by high emotional and economic instability levels, rendering increased susceptibility to distress and propensity to engage in addictive behavior. This study aims to investigate the association between parental divorce and smoking dependence among Lebanese adolescents, along with exploring the potential mediating effect of mental health disorders of such correlation. Methods A total of 1810 adolescents (14 and 17 years) enrolled in this cross-sectional survey-based study (January-May 2019). Linear regressions were conducted to check for variables associated with cigarette and waterpipe dependence. PROCESS v3.4 model 4 was used to check for the mediating effect of mental health disorders between parental divorce and smoking dependence. Results Higher suicidal ideation and having divorced parents vs living together were significantly associated with more cigarette and waterpipe dependence. Higher anxiety was significantly associated with more waterpipe dependence. Insomnia and suicidal ideation played a mediating role between parental divorce and cigarette/waterpipe dependence. Conclusion Our results consolidate the results found in the literature about the association between parental divorce and smoking addiction and the mediating effect of mental health issues. We do not know still in the divorce itself or factors related to it are incriminated in the higher amount of smoking in those adolescents. Those results should be used to inspire parents about the deleterious effect of divorce on their children to lower their risk of smoking addiction. Further longitudinal studies are needed to better understand the complexity of such associations and to see whether the divorce experience by itself or the factors that accompany it are involved in the increased smoking addiction among adolescents.